RELASI SOSIAL DOKTER DALAM PELAYANAN KESEHATAN PASIEN (Studi Tentang Hubungan Sosial Dokter Dengan Pasien di Poliklinik Rumah Sakit Umum Daerah dr. Zainoel Abidin, Banda Aceh) - Chindi Putri Chaniago; Bahrein T. Sugihen (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
ABSTRAKSalah satu masalah kesehatan di Indonesia adalah pelayanan kesehatan dokter kepada pasien di rumah sakit, dokter sudah bertindak sebagai kelompok professional yang berlandaskan pada standar operasional dokter dan rumah sakit tempat bekerja. Akan tetapi, masih ada pasien dan keluarga pasien yang merasa pelayanan kesehatan dokter di rumah sakit masih kurang memadai. Penelitian ini bertujuan untuk mendeskripsikan relasi sosial dokter dalam pelayanan kesehatan pasien di Rumah Sakit Umum Daerah Zainoel Abidin (RSUDZA), Kota Banda Aceh. Teori yang digunakan dalam penelitian ini adalah interaksionisme simbolik George Herbert Mead. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif dengan melakukan wawancara semi terstruktur kepada informansebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa,relasi sosial dokter dan pasien dalam pelayanan kesehatan di RSUDZA menggunakan relasi sosial pemaknaan atas simbol-simbol dokter sebagai kelompok professional yang bermakna superior bagi dokter sendiri dan juga pasien, sedangkan makna atas simbol pasien adalah kelompok yang membutuhkan pertolongan medis dokter. Sehingga, timbul relasi sosial dokter dan pasien atas makna tersebut yang tidak seimbang, dimana dokter sangat aktif sedangkan pasien pasif dalam mengupayakan kesembuhan pasien.Semua ini tertuang dalam bentuk tindakan atas pemaknaan simbol relasi antara dokter dan pasien dalam pelayanan kesehatan, dimana sikap kritis pasien yang terpendam karena pemaknaan pasien sendiri terhadap simbol dokter sebagai kelompok professional yang superior dan sikap kepatuhan pasien terhadap instruksi dokter sangat dipengaruhi oleh pemaknaan dokter oleh pasien.Kata Kunci :Relasi Sosial, Dokter, Pasien, Pelayanan Kesehatan.The Doctor's Social Relations in The Patient's Health Service (The Study of Doctor in Polyclinics RSUD dr. Zainoel Abidin, Banda Aceh)ABSTRACTOne of the health problems in Indonesia is doctor's health services to patients in the hospital. The doctors have acted as a professional group based on the doctor and hospital standard operationwhere they work. However, there are still patients and families of patients who feel that health service provided by the doctors in hospitals are still inadequate. Therefore, this study aimed to describe the social relation of the doctor in providing the health services to patients in the dr. Zainal Abidin General Hospital (RSUDZA), Banda Aceh. The theory used in this research is the symbolic interactionism of George Herbert Mead. This research employed descriptive-qualitative approach. Asemi-structuredinterview with the informantswas usedas the data collection technique. The results of the research showed that social relation between doctor and patient in the health service at RSUDZA was in the form of symbols where thedoctor is regardedas a professional group that is superior to both the doctor and the patient, and the patients as a group that needs medical help from a doctor. The social relation between the doctor and patient was unbalanced. The physician was very active while the patient was passive in seeking healing.There was a cooperation between the doctor and patient. It could be seen from the information exchange between them with the aim to diagnose a patient’s illness through consultation and treatment. There were openness, empathy, and positivity when the health care process takes place. However, equality between physicians and patients was still lacking. The social relationship between physician and patient occurs because of the importance of the doctor to diagnose the patient's illness and the patient's interest in the perceived illness.All of this was materialized in the form of action on the meaning of the symbol of the relation between the doctor and the patient in the health service. The patient's critical attitude is latent due to the patient's meaning of the symbol of doctors as a superior professional group and the patient's compliance with the doctor’s instruction was strongly influenced by the meaning of doctor by the patients. Keywords: Social Relation, Doctor, Patient, Health Service